Bioengineering and computational analysis of programmed cell death ligand-1 monoclonal antibody - Kalim, Muhammad; Ali, Hamid; Rehman, Ashfaq Ur; Lu, Yong; Zhan, Jinbiao (Frontiers in Immunology, 2022)
The B7 family trans-membrane protein Programmed cell death ligand-1 (PD-L1) binds to the Programmed death-1 (PD-1) protein and prevents T-cells from multiplying and activating, causing cell exhaustion. By blocking PD-1/PD-L1 interactions, a number of therapeutic antibodies are being used to aid T-cell proliferation. In the development of such powerful antibodies, recombinant technology appears to be highly useful. The variable-region was cloned and expressed in mammalian cell lines using the pMH3 mammalian expression vector using recombinant methods. G418 supplementation was used to screen the recombinant clones, which were then nourished on serum-free media. The full-length antibody was recovered and purified with a concentration of 0.5-0.8 mg/ml from the medium supernatant. Binding affinity was investigated using ELISA and immunofluorescence. Using a docking technique, the same protein-protein interaction mechanism was used to discover antigen-antibody interactions. The Swiss model was utilized for homology modeling, whereas ZDOCK, Chimera, and PyMOL were used to validate 3D models. The Ramachandran plots were created using the SWISS model, which demonstrated that high-quality structures had a value of more than 90%. Antigen-antibody interactions can be accurately determined using current methods.